Temperature of quasi-two-dimensional electron gases under steady-state terahertz drive - Asmar, N. G.; Cerne, J.; Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Campman, K. L.; Gossard, A. C. (Applied Physics Letters, 1996)
We use photoluminescence to study the time-average energy distribution of electrons in the presence of strong steady-state drive at terahertz (THz) frequencies, in a modulation-doped 125 Angstrom AlGaAs/GaAs square well that is held at low lattice temperature TL. We find that the energy distribution can be characterized by an effective electron temperature, T-e(>T-L), that agrees well with values estimated from the THz-illuminated, dc conductivity. This agreement indicates that under strong THz drive, LO phonon scattering dominates both energy and momentum relaxation; that the carrier distribution maintains a heated, thermal form; and that phonon drift effects are negligible. (C) 1996 American Institute of Physics.
Keywords: hot-electrons; Physics